Human occupation of the north Patagonian coast (San Matias Gulf): Current perspectives - Borella, Florencia (2015)
The North Atlantic Patagonian Coast (San Matías Gulf [SMG], Río Negro, Argentina) is known for its archaeological richness covering some 380 km of the littoral, (Figure 1). This region has evidence for early human adaptation to marine resource exploitation. This was the focus of early studies undertaken by Dr. Bórmida in 1961 and 1966, within the framework of the Vienna Culture-Historical School. These studies described mainly surface lithic material; these were then employed in defining ?industries?, and subsequently used to characterize the prehistoric groups in the area across successive phases over a period of some 6,000 years. Nevertheless, these pioneering archaeological studies along the Río Negro coast were discontinued in the following four decades. This then created an information ?vacuum? concerning the archaeology of this region that lasted until 2004. In that year we undertook new studies into the area focusing on several research strands: distributional and lithic studies, paleoenvironmental, isotope and zooarchaeological analyses, and the creation of a firm chronological framework. We summarize these results and advances below, who changed the traditional prehistoric view of "guanaco hunter-gatherer" in continental Patagonia, providing sufficient evidence to support the presence of land-shellfishers-gatherer groups in this coastal sector at least during the end of the middle Holocene.